A Practical Method to Estimate Entrepreneurship's Reward - Miltiades N. Georgiou (Max Planck Institute of Economics, 2005)
In the present note, an effort will be made for a contribution to the economic theory by introducing a practical method to estimate entrepreneurship's reward. As an example, a regression, based on the estimation of entrepreneurship's reward, with baning panel data will yield the same main results as in the article of Governance Structures, Efficiency and Firm Profitability, by E. E. Lehmann, S. Warning and J. Weigand, MPI, that firms with more efficient governance have higher profitability.
Keywords: E50; L25; M13; 330; bank; profitability; entrepreneurship